Pengembangan E-Book Mindfulness Model Addie untuk Meningkatkan Self-Regulation Peserta Didik - Arbain Fajar A. Hamid; Sahril Buchori; M. Amirullah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
The low self-regulation ability among vocational high school (SMK) students is a fundamental problem affecting learning effectiveness and career readiness. This study aims to develop a mindfulness e-book as a guidance media to improve students' self-regulation, encompassing needs analysis, prototype development, validity testing, and practicality testing. The research employed a Research and Development (R&D) method using the ADDIE model, conducted at SMK Negeri 3 Makassar involving a number of students in the analysis phase, several expert validators, one school counselor, and a small group of students in the trial phase. Analysis results revealed that the majority of students had low self-regulation, with primary issues identified in the aspects of impulse control and goal setting. The e-book was developed across five chapters based on mindfulness aspects with proportional exercise distribution aligned to empirical needs analysis findings. Validity assessments by content and media experts yielded a highly valid category, while practicality evaluations by both the school counselor and students were entirely categorized as highly practical. The e-book is proven to meet quality standards as a valid and practical mindfulness intervention media for counseling and guidance services in vocational schools.